Strategi Guru Ilmu Pengetahuan Sosial dalam Mengoptimalkan Aspek Afektif Peserta Didik di SMPN 8 Pamekasan - Agung Widiyanto Santoso; Sahrul Romadhon (IAIN Madura, 2021)
The teacher's strategy in optimizing the affective aspects of students is a very important thing in education because the affective aspects will relate to the interests and attitudes of students in learning. This study aims to determine the strategies of social studies teachers in optimizing the affective aspects of students at SMPN 8 Pamekasan, to determine the impact of implementing the social studies teacher strategies in optimizing the affective aspects, and the supporting and inhibiting factors in the social studies teacher strategies in optimizing the affective aspects of students. This study uses a qualitative approach to the type of phenomenological research. From this research, it is known that there are several strategies that social studies teachers use in optimizing the affective aspects of students, starting from pre-learning, during learning and post-learning, all of which is done in order to get optimal learning outcomes from students at school.